The Rights to Marry, Property and Be Free from Torture: A Study on the Elderly of Rajshahi District in Bangladesh - A K M Mahmudul Haque; Md. Zahid Hossain; S M Akram Ullah (Khazanah Sosial, 2022)
Everybody deserves the right to marry, the right to property, and the right to be free from torture as fundamental rights. These rights are preserved by the state and have been incorporated in the constitution of the People’s Republic of Bangladesh. These are also recognized by the Universal Declaration of Human Rights (UDHR) as fundamental rights. This study is an endeavor to depict a clear picture of human rights violation of the elderly people of a northern district of Bangladesh in the aspect of the right to marry, the right to property, and the right to be free from torture. These rights are very important for a human being and it is the responsibility of the state to protect these rights according to the highest law of Bangladesh. But the study found that these rights are often violated in several ways in the study area. Lack of ethical views, corruption, and weakness of law enforcement are the main hindrances responsible for this case. This research is based on both primary and secondary data. It recommends some suggestions to out away these impediments. Raising proper familial education with morals and values is very important in this sphere. The government has to be more active in the ground of law enforcement and social movement should be built massively against corruption.